Features of the analysis of economic activity in the organizations of agro-industrial complex (Journal of Economic Research & Business Administration, 2017)
Results of work of the entities of agricultural industry considerably depends on a production condition.Therefore the economic analysis begins with studying of climatic conditions, the size of a productionorientation, level of intensifications of production and its efficiency. Only taking into account specificcircumstances it is possible to estimate objectively results of activities of the entity and to determineit ways of further development. Conditions of production can be divided into three groups: climaticconditions, economy location, economic situation of production. Each of these groups is characterizedby the corresponding system of indicators.In article features of the economic analysis of activities of agricultural organizations and each featurewhich enters into group are divided into two groups it is specifically shown. At the same time the acceptancesand methods applied in the analysis of results of works of agricultural industry, indicators ofstudying of level of an intensification of production are determined.